A decade of logistics education research in the era of industry 4.0: A literature review on trends, challenges, and curriculum development - Darmawan, Bambang; Puspanikan, Saskia Kanisaa; Permadi, Dodi; Sukmayanti, Lia (Jurnal Pendidikan Teknologi Kejuruan, 2025)
The industry 4.0 era has transformed logistics education by integrating advanced technologies such as artificial intelligence, Internet of Things, and big data analytics. The substantial gap between the competencies taught in educational institutions and the needs of the modern logistics industry demonstrates the need for a comprehensive analysis of the development of logistics education research. This research aims to analyse development trends, identify implementation challenges, and formulate strategies for the development of Industry 4.0 responsive logistics education curriculum. The systematic literature review method using the PRISMA framework was applied to 20 high-quality articles from the Scopus, Heliyon, Emerald Insight, Taylor & Francis Online, and SpringerLink databases for the period 2020-2025. The results of the study show a paradigmatic transformation from conventional approaches towards comprehensive digital technology integration, with research methodologies evolving from quantitative surveys to empirical analysis based on advanced technology. Implementation challenges include limited technological infrastructure, lecturer competency gaps, and varying student readiness. The conclusion of the study reveals the need for a holistic learning framework that integrates six main drivers with flipped classroom approaches and Outcome-Based Education. Curriculum development suggestions should integrate sustainability, resilience, and green innovation perspectives to prepare competent graduates to face the global logistics industry revolution.